PELAKSANAAN KEGIATAN EKSTRAKULIKULER TILAWAH DALAM MENGEMBANGKAN BAKAT SANTRI DI PONDOK PESANTREN NURUDLUHA - Faturrohmah, Heni; Mufidah, Lu’luul (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2025)
Education in Islamic boarding schools does not only emphasize the teaching of religious knowledge, but also plays a role in developing the interests and talents of students, both academic and non-academic. Based on Gardner's theory of multiple intelligences, each individual has different potentials that can be developed through the right approach, one of which is through extracurricular activities. This study aims to describe the implementation of extracurricular tilawah at Nurudluha Islamic Boarding School, including management, implementation, and program evaluation. The approach used is descriptive qualitative with interview, observation, and documentation techniques. The results of the study indicate that tilawah activities are carried out systematically with the talaqqi musyafahah method and supported by adequate facilities. This activity is able to improve the ability to read the Qur'an, build self-confidence, and develop the art of tilawah. Although this activity has a positive impact on the development of students' talents, there are still obstacles in the form of limited space to appear in official forums and the absence of efforts to involve students in competitions. Therefore, further policies are needed to expand student participation and encourage more optimal coaching sustainability.